2022
DOI: 10.1186/s40494-022-00696-4
|View full text |Cite
|
Sign up to set email alerts
|

Visualising iron gall ink underdrawings in sixteenth century paintings in-situ by micro-XRF scanning (MA-XRF) and LED-excited IRR (LEDE-IRR)

Abstract: Until today, iron gall ink is classified as an exceptional underdrawing material for paintings. Its study and definite identification is usually based on invasive analysis. This article presents a new non-destructive approach using micro-X-ray fluorescence scanning (MA-XRF), LED-excited IRR (LEDE-IRR) based on a narrow wavelength-range of infrared radiation (IR) for illumination and stereomicroscopy for studying and visualising iron gall ink underdrawings. To assess possibilities and limits of these analytical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…IR reflectography actually highlighted two different techniques of underdrawings: a pouncing technique was likely used for the cardinals (although hardly visible) and freehand drawing with black chalk for the pope [52]. Recently, works exploiting MA-XRF on paintings have, interestingly, found that the distribution of Zn detected in paintings is most likely related to iron-gall-ink underdrawings [53,54]. Unfortunately, the dwell time of the measurements carried out here does not give a sufficient resolution for a proper identification based on the visualization of characteristic features of underdrawings such as hatching, but the use-not yet documented in Raffaello's painting-of iron-gall ink as underdrawing remains an intriguing possibility.…”
Section: Resultsmentioning
confidence: 99%
“…IR reflectography actually highlighted two different techniques of underdrawings: a pouncing technique was likely used for the cardinals (although hardly visible) and freehand drawing with black chalk for the pope [52]. Recently, works exploiting MA-XRF on paintings have, interestingly, found that the distribution of Zn detected in paintings is most likely related to iron-gall-ink underdrawings [53,54]. Unfortunately, the dwell time of the measurements carried out here does not give a sufficient resolution for a proper identification based on the visualization of characteristic features of underdrawings such as hatching, but the use-not yet documented in Raffaello's painting-of iron-gall ink as underdrawing remains an intriguing possibility.…”
Section: Resultsmentioning
confidence: 99%
“…The former irradiates the sample, and the latter collects the fluorescence signal emitted by the sample. In principle, no other requirements are needed; for this reason, XRF can be conducted in situ, directly on the artifact [35][36][37][38][39][40][41], without the need for sample transportation. Due to the absorption of air and the detector efficiency, XRF can generally detect atoms heavier than silicon, up to uranium; however, some spectrometers can detect elements as light as fluorine [42].…”
Section: Introductionmentioning
confidence: 99%